Rangelands restoration analysis in Southern Al-Jabal Al-Akhdar, Libya using landscape function analysis and selected vegetation indicates - Mahmoud, Adel M. A. (2016)
Many regions in Libya have begun to show signs of rangelands degradation, the major causes of which are drought and overgrazing.It has been documented that rangelands deterioration has led to a reduction in the variety of plants and a decrease in yield, and this decreases the regenerative capacity of rangeland ecosystem. This study was conducted on the southern slope of Al- Jabal Al- Akhdar, northeast Libya.The main objective was to assess shrub rangeland recovery to determine whether or not exclosures (fenced areas) are an effective method or strategy for the restoration and rehabilitation of rangelands at the regional level.Four research areas with moderate to severe degraded soil and vegetation, namely Madur Zetun, Omguzlan, Thahar Altair, and Ajramiah, were selected along a strong north-south rainfall gradient, which include a diverse range of soil and vegetation types. A total of 28 monitoring sites were re-installed and assessed between May and December 2014. These sites were initially installed and assessed between May and December 2006. The monitoring sites were installed within the exclosures and in open rangelands for grazing. The monitoring layout is based on the Western Australia Rangeland Monitoring System (WARMS). In order to achieve the research objective,Landscape Function Analysis technique (LFA) and selected Vegetation Indices (VIs)were employed.The outcomes of the LFA field data calculations show that the ecosystem function increased positively with the increase in rehabilitation time of the protected areas where fences is taking places. The results also indicate an increase in the three indices of soil surface condition (SSI, WII and NCI) inside the fenced rangelands. The findings demonstrate a good linear relationship between the LFA-SSA indices and the selected Vegetation Indices. NDVI (Normalized Difference Vegetation Index) and MSAVI (Modified Soil-Adjusted Vegetation Index) were closely correlated to the field data.Additionally, the results indicate that the vegetation cover did not change or increase in a large portion of the regions under study even with 80% of the study area still under severe to very severe conditions of degradation. Finally, estimates show that a period of 10 years, meant to protect the vegetation from animal grazing may be needed in the higher rainfall location at the north (Maduar Zetun).Regions that experience low rainfall situated in the south prior to the recovery of vegetation, and soil surface condition at the time of grazing, require a long period of protection. Grazing must be controlled to facilitate the conservation and rehabilitation of rangeland natural resources.